2017
DOI: 10.1016/j.aninu.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with sugar cane extract on meat quality and oxidative stability in finishing pigs

Abstract: The aim of the present study was to investigate the effect of dietary supplementation with sugar cane extract (SCE) on meat quality and oxidative stability of Longissimus dorsi muscle in finishing pigs. Eighteen barrows (Duroc × Landrace × Jiaxing Black), with an average initial body weight of 62.1 ± 5.0 kg, were randomly allotted to 1 of 3 diets with 6 replicates per treatment for 42 days. The diets comprised a normal diet and the normal diets supplemented with 5 and 25 g/kg SCE. The results showed that SCE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
(30 reference statements)
0
11
0
1
Order By: Relevance
“…and endogenous antioxidative enzymes (SOD, CAT, GSHPx, etc.). GSH, SOD, CAT and GSHPx play an important role in the protection of meat quality (Xia et al 2017;Cheng et al 2017). Some studies have shown that the post-slaughter muscle antioxidant system can decrease the concentrations of free radicals to inhibit the oxidation of polyunsaturated fatty acids, thus affecting the shelf-life of pork and maintaining the meat quality (Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…and endogenous antioxidative enzymes (SOD, CAT, GSHPx, etc.). GSH, SOD, CAT and GSHPx play an important role in the protection of meat quality (Xia et al 2017;Cheng et al 2017). Some studies have shown that the post-slaughter muscle antioxidant system can decrease the concentrations of free radicals to inhibit the oxidation of polyunsaturated fatty acids, thus affecting the shelf-life of pork and maintaining the meat quality (Chen et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…• Efeito imunoestimulante e ação preventiva contra o vírus da pseudo-raiva, enfermidade infecto contagiosa grave (Lo et al, 2005(Lo et al, , 2006 • Efeito antioxidante mensurável na qualidade da carne de porco (Xia et al, 2017).…”
Section: Propriedades Terapêuticasunclassified
“…Sugarcane can be consumed in the form of juice, syrup, dried sugar or molasses, while the sucrose extracted in mills can be used as a raw material in the food industry. Fresh-chopped sugarcane or extracts may be used as a dietary supplement for ruminants or pigs under limited forage availability [116]. Considering this variety of uses, we observe that different sweet potato varieties, as well as sugarcane and corn varieties, may be suited to the production of certain outputs (and related by-products), opening up a wide range of new market opportunities for smallholder farmers.…”
Section: Water-energy-food (Wef) Considerationsmentioning
confidence: 99%